1999
DOI: 10.1111/1469-8986.3620164
|View full text |Cite
|
Sign up to set email alerts
|

The psychobiology of strained breathing and its cardiovascular implications: A functional system review

Abstract: Strained breathing is a natural respiratory pattern, with cardiovascular implications. It is associated with social factors, attention, expectation, and anxiety and with defense behavior in animals. An inhibition of active behavior is characteristic. Strained breathing is based on the functional heterogeneity of the medullary postinspiratory neurons. In stressful circumstances, muscle tension and laryngeal reflexes induce a strong reduction of airflow in the glottis, resulting in a prolonged Stage I of expirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 104 publications
(153 reference statements)
0
5
0
1
Order By: Relevance
“…Left and right side muscle EMG data were averaged abdominus) may be the first to contract in preparation for such an activity , a certain amount of CC from all trunk muscles seems to be necessary to assure adequate stability of the lumbar spine and the rigidity of the thorax (Cholewicki et al 1999b;Cholewicki et al 1997). The elevated ITP is caused by a strong expiratory effort induced by contraction of abdominal and thoracic muscles against a closed or partially closed glottis (Fokkema 1999). Consistent with this mechanism, we found that activities of the thoracic erector spinae muscles correlated better with ITP (r=0.81) than with IAP (r=0.75).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Left and right side muscle EMG data were averaged abdominus) may be the first to contract in preparation for such an activity , a certain amount of CC from all trunk muscles seems to be necessary to assure adequate stability of the lumbar spine and the rigidity of the thorax (Cholewicki et al 1999b;Cholewicki et al 1997). The elevated ITP is caused by a strong expiratory effort induced by contraction of abdominal and thoracic muscles against a closed or partially closed glottis (Fokkema 1999). Consistent with this mechanism, we found that activities of the thoracic erector spinae muscles correlated better with ITP (r=0.81) than with IAP (r=0.75).…”
Section: Discussionmentioning
confidence: 99%
“…However, a paradoxical increase in IAP and transversus activity during trunk flexion tasks was hypothesized to increase spine stability. The observation that the transversus abdominus is recruited first among all abdominal wall muscles in the preparatory postural response to rapid limb movement in healthy individuals, but not in patients with low back pain, appears to add further importance to this muscle's function (Hodges and Richardson 1996, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Although this standard set of fear-related CRs certainly reflects important facets of (learned) fear, it is mainly representative of the socalled postencounter phase on the continuum of defensive responding, during which an organism reduces physical activity and directs attention to an environmental stimulus (Lang & Bradley, 2013). Attentional responses are sometimes characterized by a decrease in cardiorespiratory activation (Denot-Ledunois, Vardon, Perruchet, & Gallego, 1998;Fokkema, 1999;Obrist, Webb, & Sutterer, 1969;Stekelenburg & Van Boxtel, 2002;Van Diest et al, 2009). Panic attacks, in contrast, are thought to reflect acute, massive bursts of cardiorespiratory arousal and energy mobilization to support overt, action-oriented defensive responses (fighting, fleeing) to imminent threat.…”
Section: Conditioned Responsementioning
confidence: 99%
“…Similarly, increases in FRC have been observed during posing of emotional facial expressions, which was related to ratings of effort and heart rate accelerations (Boiten, 1996). It is conceivable that a variety of behavioral adaptations such as inhibition, attention, effort, or defensive coping would involve breathing at altered FRC (i.e., hyperinflation) (see also "strained breathing, " Fokkema, 1999). Elevated inspiratory muscle activity during expiration would be a key mechanism in generating such alterations in breathing pattern, but the autonomic concomitants as well as the short-and long-term costs of these adaptations for the organism have not been explored sufficiently.…”
Section: Introductionmentioning
confidence: 88%